The Frequency of Cervical Lymph Node Metastasis in Multifocal Papillary Thyroid Carcinoma - FAIZA SIDDIQUE, TOOBA MAHMUD, ASHFAQ AHMAD (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the frequency of metastatic cervical lymphadenopathy among cases presented with multifocal papillary thyroid carcinoma (PTC) planned to undergo total thyroidectomy (TT) with or without neck dissection. Materials and Methods: A retrospective study was conducted based on data of 35 patients who presented with PTC and had been managed at East Surgical ward, Mayo Hospital ,Lahore from August 2010 to April 2011. Data of 35 patients of PTC was collected from inpatient department of East Surgical ward. Confidentiality of information was ensured. All the patients underwent total thyroidectomy with or without cervical lymph node dissection. Results: Of these 35 patients, 11 had multifocal PTC proven on histopathology. Among these multifocal tumors, cervical lymphadenopathy was identified in 6 (54.5%) patients and underwent neck dissection . Remaining 5 cases did not have lateral neck nodes so underwent T.T only. Post operative recurrence was noted in 1 patient who had not undergone neck dissection. Conclusion: In present case series, cervical lymph node involvement is significantly higher in multifocal tumors and recurrence in cervical lymph nodes is significantly related to tumor multi focality. As central compartment lymph nodes are first to be affected by metastasis from PTC, so prophylactic central compartment dissection should be carried out in patients having multifocal tumors